Effects of low dose ibogaine on subjective mood state and psychological performance - Forsyth, Bridget; Machado, Liana; Jowett, Tim; Sonntag, Hannah; Garbe, Kira; Winter, Helen; Glue, Paul (Journal of ethnopharmacology, 2016)
Ethnopharmacological relevance - Root bark from Tabernanthe iboga has been used traditionally in West Africa as a psychoactive substance in religious rituals. In smaller doses it is reported anecdotally to have stimulant properties. - Aim of the study - To evaluate the influence of a single 20mg ibogaine dose on psychological variables reflecting subjective mood state and a range of cognitive functions. - Materials and methods - 21 healthy male volunteers received single 20mg doses of ibogaine after 6 days pretreatment with double-blind paroxetine or placebo. We compared responses to a battery of psychometric tests and subjective mood ratings performed before and 2h after ibogaine dosing, and assessed relationships between changes in test scores and concentrations of active moiety (the sum of molar noribogaine and ibogaine concentrations). Psychological tests were chosen based on responsiveness to opioid and serotonergic ligands. - Results - Ibogaine had minimal influence on psychological tests and mood ratings. The ability to selectively ignore distracting spatial information showed some evidence of modulation; however because this effect was limited to the less challenging condition calls into question the reliability of this result. - Conclusion - We were unable to identify stimulant effects after single 20mg doses of ibogaine. Future research is needed to confirm whether active moiety concentrations impact selective attention abilities while leaving other cognitive functions and mood state unaffected.
Gesehen am 22.05.2020